2016
DOI: 10.1038/srep36520
|View full text |Cite
|
Sign up to set email alerts
|

Axl is required for TGF-β2-induced dormancy of prostate cancer cells in the bone marrow

Abstract: Disseminated prostate cancer (PCa) cells in the marrow survive for years without evidence of proliferation, while maintaining the capacity to develop into metastatic lesions. These dormant disseminated tumor cells (DTCs) may reside in close proximity to osteoblasts, while expressing high levels of Axl, one of the tyrosine kinase receptors for growth arrest specific 6 (Gas6). Yet how Axl regulates DTC proliferation in marrow remains undefined. Here, we explored the impact of the loss of Axl in PCa cells (PC3 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
135
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 144 publications
(138 citation statements)
references
References 46 publications
3
135
0
Order By: Relevance
“…In retrospect, it would have been useful in include MERTK in these studies. Our most recent work, currently in press, confirms the earlier hypothesis regarding AXL and shows that AXL is required for TGF-β2 induced prostate cancer dormancy(Yumoto 2016). However, prior to the current work, the contribution of MERTK to prostate cancer dormancy remained completely unclear.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In retrospect, it would have been useful in include MERTK in these studies. Our most recent work, currently in press, confirms the earlier hypothesis regarding AXL and shows that AXL is required for TGF-β2 induced prostate cancer dormancy(Yumoto 2016). However, prior to the current work, the contribution of MERTK to prostate cancer dormancy remained completely unclear.…”
Section: Discussionsupporting
confidence: 87%
“…However, these studies did not include experiments to test this hypothesis further than gene expression. Most recently, in work that is currently in press, we reported that AXL is required for TGF2 to induce prostate cancer dormancy (Yumoto 2016). However, the contributions of MERTK and TYRO3 remain unclear.…”
mentioning
confidence: 99%
“…Previously we have observed that GAS6 expression by osteoblasts regulates PCa dormancy through interactions with MERTK (8,29,30,33). First, we sought to confirm the GAS6 mRNA results at the protein level.…”
Section: Resultsmentioning
confidence: 97%
“…Previously we determined that when PCa cells become proliferatively quiescent when co-cultured with osteoblasts (8,29,30). To determine whether NE is able to alter the quiescence of PCa cells induced by osteoblasts, co-culture experiments were performed where in the human PCa cells were selectively analyzed using antibodies specific for human HLA.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation